A short history of mediastinal tumours - Evaggelia Grisbolaki; Vasileios Leivaditis; Konstantinos Grapatsas; Efstratios Koletsis; Francesk Mulita; Maria Flouri; Dimos Gravanis; Georgios Vakis; Ioannis Panagiotopoulos; Manfred Dahm; Georgios-Ioannis Verras; Konstantinos Tasios; et al. (Termedia Publishing House, 2023)
The mediastinum constitutes an area of special surgical interest due to important anatomical relationships and histopathologic variability of mediastinal primary and metastatic tumours. Mediastinum was considered inaccessible until the end of the 19th century. For many decades the diagnosis of mediastinal disease relied solely upon clinical presentation, and the mainstay of treatment was medical therapy. The advancements in radiology and intraoperative ventilatory support facilitated the improvement of certain diagnostic and therapeutic approaches to mediastinal disease.